Anxiety and 10-Year Risk of Incident Dementia—An Association Shaped by Depressive Symptoms: Results of the Prospective Three-City Study - Mortamais, Marion; Abdennour, Meriem; Bergua, Valérie; Tzourio, Christophe; Berr, Claudine; Gabelle, Audrey; Akbaraly, Tasnime N. (Frontiers in Neuroscience, 2018)
Background: Anxiety is common in patients with cognitive impairment and dementia. However, whether anxiety is a risk factor for dementia is still not known. We aimed to examine the association between trait anxiety at baseline and the 10-year risk of incident dementia to determine to which extent depressive symptoms influence this relationship in the general population. Methods: Data came from 5,234 community-dwelling participants from the Three-City prospective cohort study, aged 65 years at baseline and followed over 10 years. At baseline, anxiety trait was assessed using the Spielberger State-Trait Anxiety Inventory (STAI), and depressive symptoms using Center for Epidemiologic Studies-Depression Scale (CESD). Use of anxiolytic drugs was also considered. Diagnoses of dementia were made at baseline and every 2 years. To examine the relationship between anxiety exposures and risk of incident dementia, Cox proportional hazard regression models were performed. Results: Taking anxiolytic drugs or having high trait anxiety (STAI score ≥ 44) increased the risk of dementia assessed over 10 years of follow-up [Hazard Ratio (HR) = 1.39, 95%CI: 1.08–1.80, p = 0.01 and HR = 1.26, 95%CI: 1.01–1.57, p = 0.04, respectively], independently of a large panel of socio-demographic variables, health behaviors, cardio-metabolic disorders, and additional age-related disorders such as cardiovascular diseases, activity limitations, and cognitive deficit. However, the associations were substantially attenuated after further adjustment for depressive symptoms. Conclusion: Our findings suggest that depressive symptoms shape the association between anxiety trait and dementia. Further research is needed to replicate our findings and extrapolate our results to anxiety disorders.